Status of antibiotic residues and detection techniques used in Chinese milk: a systematic review based on cross-sectional surveillance data - Lu, Guangyu; Chen, Qi; Li, Yuping; Liu, Yuting; Zhang, Yuying; Huang, Yujia; Zhu, Lei (Food research international, 2021)
Antibiotic residues (ARs) in food of animal origin are of worldwide concern, particularly in China, the world’s largest producer and consumer of antibiotics. Aiming to provide a reference for the use of antibiotics in dairy cows, for supervision and management departments in the detection of related antibiotics, and for guiding the safe use of antibiotics in food, this systematic review was carried out to determine the prevalence of ARs and antibiotic detection techniques in Chinese milk over the past three decades. The systematic review follows the PRSIMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Both English (Cochrane, Embase, MEDLINE, PubMed, and Web of Science) and Chinese databases (Chinese National Knowledge Infrastructure, China Science and Technology Journal Database, and WanFang Database) were systematically searched, from inception to 31 July 2020. Among the 3131 citations screened, 46 active surveillance cross-sectional studies published between 1988 and 2020 in 26 Chinese provinces were eligible, providing antibiotic levels for a total of 8788 milk samples. Although the AR rates in fresh and sterilized milk fluctuate, they have largely declined in recent years. Among the 18 evaluated antibiotics, sulfamethoxazole, chloramphenicol, and trimethoprim are primary antibiotics with high residual rates. The most frequently used technique to monitor antibiotic levels in milk is 2,3,5-Triphenyltetrazolium chloride (TTC) staining. This review confirmed the importance of food safety monitoring and surveillance systems in preventing antibiotic exceedances in food. Several lessons learned from antibiotic surveillance and supervision in China were revealed. The provision of education to rural farmers should be strengthened to enhance their knowledge on antibiotic use in animal agriculture. Moreover, a standard operational protocol for screening and targeting antibiotics in dairy products should be considered to increase the comparability between cross-sectional active surveillance studies of AR in milk.